Spiritual Support and Parental Communication on Perceptions of HIV Prevention in Adolescents - Angela Librianty Thome; Viere Allanled Siauta; Fenska Narly Makualaina (GLOBAL HEALTH SCIENCE GROUP, 2026)
Adolescents are a group vulnurable to HIV transmission due to limited knowledge and strong social influences. Adolescents’ perceptions of HIV prevention are greatly influenced by internal and external factors, including spiritual support and communication with parents. Spiritual support can strengthen moral values and self-responsibility, while parental communication plays a role in providing accurate information and guidance. This study aims to spiritual support and parental communication on adolescents’ perception of HIV prevention. This study used a cross-sectional design with a total sampling of 31 adolescent respondent. Data collection was conducted using a Likerts scale questionnaire to assess spiritual support, parental communication, and perceptions of HIV prevention. Data analysis was perfomed using multiple linear regression tests with a significance level of <0.05. The analysis results showed that spiritual support had no significant effect on perceptions of HIV prevention (p = 0.969), not did parental communication (p = 0.469). Simultaneous testing showed that both variables together did not significantly influence perceptions of HIV prevention. Spiritual support and parental communication did not significantly influence adolescents' perceptions of HIV prevention. HIV prevention efforts need to consider a spiritual approach and strengthen family communication to shape healthy perceptions and behaviors in adolescents.